COVID-19 Surveillance in the Primary Health Care Population of Qatar: Experience of Prioritizing Timeliness Over Representativeness When Sampling the Population - A/Qotba, Hamda Abdulla; Al Nuaimi, Ahmed Sameer; Al Mujalli, Hanan; Zainel, Abduljaleel Abdullatif; Khudadad, Hanan; Marji, Tamara; Veettil, Shajitha Thekke; Syed, Mohamed Ahmed (Frontiers in Public Health, 2021)
SARS-CoV2 a new emerging Corona Virus Disease in humans, which called for containment measures by many countries. The current paper aims to discuss the impact of two different sampling methodologies applied when executing a drive through COVID19 survey on the quality of estimated disease burden measures. Secondary data analysis of a pilot cross-sectional survey targeting the primary health care registered population of Qatar was done. Two groups with different sampling methods were compared for estimating COVID19 point prevalence using molecular testing for nasopharyngeal swabs. The first group is a stratified random sample non-proportional to size (N=841). A total of 16 population strata based on age group, gender, and nationality were sampled. The second group is the Open invitation group (N=260). The results showed that the two groups were obviously and significantly different in age and nationality. In addition, reporting of COVID19 symptoms was more frequent in the open invitation group (28.2%) compared to the random sample (16.2%). The open invitation group overestimated the symptomatic COVID19 prevalence rate by more than 4 times, while the random sample group detected more asymptomatic COVID19 cases. The overall prevalence rate of active COVID19 cases in the open invitation sample (13.3%) was almost double that of the random sample (6.9%). Furthermore, using population sampling weights reduced the prevalence rate to 0.8%. The lesson learned here is it is wise to consider the magnitude of bias introduced in a surveillance system when relying on convenient sampling approaches in response to time constraints.